Improving Arabic Vocabulary Mastery with a Constructivist Approach through Mind Map: Meningkatkan Penguasaan Kosakata Bahasa Arab dengan Pendekatan Konstruktivis Melalui Mind Map - Ni'am Fadina Istiqomah; Muhammad Afif Amrulloh; Essam Mustafa Ahmed (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
A Arabic language learning, especially in understanding Arabic vocabulary at MTs Abu Bakar Ashshiddiq Lampung Utara is still relatively minimal and is constrained by low student enthusiasm for learning, as well as students' difficulties in understanding Arabic itself, so that innovation is needed in interesting learning methods to help students understand Arabic vocabulary. The purpose of the study was to analyze and evaluate the effectiveness of mind map on improving students' mastery of Arabic vocabulary with a constructivist learning approach. The type of research used is classroom action research with the Kurt Lewin model. The research data sources were obtained from the results of observations and interviews, and written tests. The test serves to assess the level of student understanding in understanding Arabic vocabulary. The respondents of this study involved 27 seventh grade students. The test was used to measure students' ability to understand Arabic vocabulary. The results of the study proved an increase in student learning outcomes in cycle I of 59.26% with an increase in cycle II reaching 85.18%. This study proves that the application of mind map integrated with constructivist approach is effective for learning Arabic vocabulary. This research can be used in other subjects. Keywords: Arabic Vocabulary, Constructivist, Mind Mapping.